ChemInform Abstract: Cu(I)/Ag(I)‐Mediated Decarboxylative Trifluoromethylation of Arylpropiolic Acids with Me3SiCF3 at Room Temperature. Issue 43 (7th October 2016) - Yang, Lingling; Jiang, Linlin; Li, Yaming; Fu, Xinmei; Zhang, Rong; Jin, Kun; Duan, Chunying
Abstract: The method allows a direct approach to the target compounds and various functionalities are tolerated.